Faces of the Peaceable God: Religious Imaginaries and the Challenge of Peace in Colombia - Gutiérrez González, Eduardo F. (Zygon, 2025)
After more than fifty years of civil conflict and nearly a quarter million casualties, Colombia finally signed a peace agreement in 2016. Subsequently, a Truth Commission was tasked with producing a report to provide a new political narrative to address the conflict, suggest ways to warrant non-repetition of atrocities, and foster peaceful coexistence. The report frequently refers to "social imaginaries" as key and hints at communities of faith as having an important peacebuilding role; however, it leaves multiple questions open. How are these imaginaries structured? How are they formed and transformed? How can religious imaginaries actively contribute to peace? This article seeks to (a) highlight important aspects of Colombia’s current political landscape and its intellectual opportunities, (b) outline a cross-disciplinary approach to develop a theory on the [trans]formation of imaginaries, and (c) illustrate how this theory can shed light on the role of religious imaginaries in Colombia, enhancing their contribution to the cultural transformations necessary for lasting peace.